T-Lymphocytes Subsets in inactive carrier state of HBV - Walaa Najim Abd alwahed; Shaymaa Hussein Hassan (World Journal of Experimental Biosciences, 2013)
This study included nine patients with inactive carrier states of HBV and 14 healthy control groups. The number and the percentage of T-lymphocyte (CD3+ Cells) in the peripheral blood of these groups showed no significant difference. Similar trend was observed when number and percentages of T helper cells (CD4+ cells) and T cytotoxic lymphocytes (CD8+ cells). Moreover, no significant difference in CD4+ /CD8+ cells ratio (P > 0.05) in peripheral blood of patients with inactive carrier state of HBV as compared with healthy control group. The levels of total serum bilirubin (TSB) concentration and alanine aminotransferase (ALT) activity were similar to control group. The levels of immunoglobulin concentration (IgG and IgM) in patients group were similar to control group. No remarks of autoimmune phenomena were observed in patients group.
Keywords: CD4+ cells; CD8+ cell; cells; Inactive carrier; HBV; T-Lymphocytes.